(untitled) (Applied Biological Research, 2023)
pilanthes acmella Murr belonging to Asteraceae is used both as an ornamental and medicinal plant. The present study was aimed to optimize Agrobacterium tumefaciens–mediated transformation of S. acmella. The bacterial density, infection period, co-cultivation temperature and acetosyringone (AS) concentration were evaluated by using leaf explants in transformation. Bacterial culture was added to 50 mL liquid YEP medium supplemented with kanamycin and rifampicin; and grown until it reached the required growth phases (A600nm). Bacterial optical density ranging from A600nm 0.15, 0.53, 1.0 and 1.5 were used. The co-cultivation medium (liquid MS medium) consisted of various concentrations of AS ranging from 100-500 μM. Histochemical analysis of β glucuronidase (GUS) gene expression was carried out in control and transformed leaf explants. Higher bacterial density resulted in more transformation efficiency, but also higher necrosis in explants. Dilution of bacterial suspension reduced necrosis in explants and resulted in higher transformation. The optimized conditions for efficient transformation were: 1:10 dilution of A600nm 0.15 bacterial density, infection period 30 min, cocultivation temperature of 22oC. The addition of AS into bacterial inoculum at 100 μM resulted in 2.5-fold increase in transformation efficiency. In future, useful genes can be introduced into S. acmella by using A. tumefaciens carrying a binary vector pCAMBIA 1301.